Featuring High Impact Polystyrene Composites Strengthened with Green Coconut Fiber Developed for Automotive Industry Application - Pereira, Gilmara Brandão; Pereira, Glayce Cassaro; Lima, Márcio; de Jesus, Brunno José Silva; de Andrade Silva, Ezequiel; Carvalho Benini, Kelly Cristina; Bandeira, Cirlene Fourquet; Montoro, Sérgio Roberto (Journal of Research Updates in Polymer Science, 2017)
Studies focused on generating products able to reduce environmental impact have been put in place, and those aiming at finding polymeric composites strengthened with natural fibers stand out among them. A composite was strengthened with coconut fibers in the present study, since the generation of coconut residues has increased in Brazil due to coconut water industrialization. The aim of the present study is to process a high impact polystyrene (HIPS) composite strengthened with coconut fiber and to verify its possible application in the automotive industry. Strengthened samples were prepared using coconut fibers in the proportions 10, 20 and 30% fiber to develop such HIPS composite. Analyses were performed in order to set the density, Shore A hardness and impact resistance of the processed composites. It was found that the density and Shore A hardness results in the HIPS did not change due to the addition of coconut fibers. However, it was observed that the impact resistance was reduced because of it. It was noteworthy that the decreased impact resistance did not preclude the use of the HIPS/coconut fiber composite, since it showed that such material can be used in parts free from strong mechanical stress such as those inside the automobiles. The use of coir HIPS also aimed at reducing costs related to the polymer’s consumption and at reusing the waste (coconut husk) from coconut water industries.